Usefulness of Background Coloration in Detection of Esophago-Pharyngeal Lesions Using NBI Magnification - Hitomi Minami; Haruhiro Inoue; Haruo Ikeda; Hitoshi Satodate; Shigeharu Hamatani; Kazuhiko Nakao; Shin-ei Kudo (Gastroenterology Research and Practice)
Background and Aim. We evaluated the usefulness of background coloration (BC), a color change in the area between intrapapillary capillary loops (IPCLs) in the early esophago-pharyngeal lesions using NBI with magnificaiton. Methods. Between April 2004 and March 2010, a total of 294 esophago-pharyngeal lesions were examined using NBI with magnification, and the presence of BC and IPCL patterns were assessed. Using BC, discrimination of squamous cell carcinoma (SCC) or high-grade neoplasia (HGN) from low-grade neoplasia (LGN) or nonatypia was conducted. Results. Among 294 lesions, 209 lesions (71.1%) were positive for BC, while 85 (28.9%) were negative. In the BC-positive group, 187 lesions (89.5%) were diagnosed as SCC/HGN. And 68 lesions (80.0%) in the BC-negative group were diagnosed as LGN/nonatypia. Overall accuracy of BC to discriminate SCC/HGN from LGN/nonatypia was 87.3%. The sensitivity and specificity were 91.9%, 76.7%. BC could discriminate SCC/HGN from LGN/nonatypia accurately (P<0.0001). Among 68 lesions classified into the IPCL type IV, the BC-positive group (n=26) included 21 SCC/HGN lesions, while there were 36 LGN/nonatypia lesions in the 42 BC-negative lesions. Conclusions. BC is a useful finding in differentiating SCC/HGN from LGN/nonatypia lesions in the esophagus especially when it is combined with IPCL pattern classification.